In Vitro anti-collagenase activity and total phenolic content of five selected herbs: a review / Siti Maisarah Shukri, Faezah Pardi and Norrizah Jaafar Sidik - Shukri, Siti Maisarah; Pardi, Faezah; Sidik, Norrizah Jaafar (Faculty of Applied Sciences, 2021)
Etlingera elatior, Persicaria odorata, Centella asiatica, Senna alata and Phyllanthus emblica were reviewed for their in vitro anti-collagenase activity and its total phenolic contents. Plant herbs play a vital role to promote the production of collagen which is the component of the skin. Different solvents during plant extraction and various plant parts were used to determine anti-collagenase properties and total phenolic content. Generally, anti-collagenase assay and Folin-Ciocalteu method were used to determine the anti-collagenase activity and total phenolic content, respectively. The extracts of these herbs have the potential of inhibiting collagenase activity and they possess total phenolic content. The total phenolic was found to be important elements in collagenase inhibition activity other than flavonoid. The selected herbs are popular in Malaysia and this review can be a useful reference or information for future application in pharmaceutical, food and cosmetics fields